Unusual presentation: fracture neck femur in 18 months old child - Patel, Chirag D.; Suthar, Pokhraj P.; Gamit, Manoj; Dave, Dhaval J. (International Journal of Research in Medical Sciences, 2017)
An 18 months old child was brought to the emergency department with alleged history of trauma due to hit by two wheeler and sustained injury over right hip. Child was not able to move the right lower limb. Physical examination of child revealed contusion over right hip region and injury over perineal region. There was no active vaginal bleeding. Rest of the systemic examination was normal. Routine blood was normal. On X-ray of pelvis with both hip showed fracture of neck femur on right side without any pelvic injury. Patient was treated with hip spica cast and complete bed rest for 1 month. After 1 month of the treatment, on follow-up the patient was able to weight bear and fractured was united on X-ray.